A COMPARATIVE STUDY TO FIND OUT IMMEDIATE EFFECTIVENESS OF MOVEMENT WITH MOBILIZATION VERSUS ELBOW ORTHOSIS ON PAIN AND GRIP STRENGTH IN LATERAL EPICONDYLITIS IN HOUSEWIVES (International Journal of Physiotherapy, 2015)
Background: There are various studies using Mulligan’s MWM with or without combining with electrotherapy modalities and proved the efficacy of the technique in immediately decreasing pain and improving grip strength in patients with lateral epicondylitis. Orthotic as a treatment is also proved to be beneficial in decreasing pain and improving grip strength. There is evidence that housewives are prone to develop lateral epicondylitis due to their routine household work. But there is lack of evidence which compare initial effects of MWM and orthosis in housewives bringing up better outcome measures. The purpose of this study is to compare the initial effectiveness of Mulligan’s MWM and elbow orthosis on pain and grip strength in housewives with lateral epicondylitis. The aim of the study is to evaluate the effectiveness of Mulligan’s MWM technique versus counterforce elbow orthosis in immediately reducing pain and improving grip strength in lateral epicondylitis in housewives.Methodos: All subjects underwent a pre-treatment examination to assess pain and pain free hand grip strength with the help of outcome measures. Subjects were randomly assigned into two groups, A and B respectively; having 25 subjects in each group. Group A was treated with one session of Mulligan’s MWM technique. Group B was treated with Counterforce elbow strap orthosis. Data was assessed pre-treatment and immediately after treatment. Visual Analogue Scale (VAS) and hand grip on Hand Grip Dynamometer (HGD) were used as outcome measures.Results: Independent t-test was performed to see the effectiveness between Mulligan’s MWM and elbow orthosis. For VAS, t = - 2.243 which is significant at 5% level of significance. It has been inferred that VAS decreases more when Mulligan’s MWM was applied. For HGD, t = 0.878 which is not significant implying that increase in HGD do not differ remarkably for the two treatments.Conclusion: It has been recorded from the study that both Mulligan’s MWM technique and counter force elbow orthosis produces significant decrease in pain and improvement in grip strength immediately after treatment. It has been seen that Mulligan’s MWM is better than counter force elbow orthosis in relieving pain (p=0.03). Increase in hand grip strength does not differ remarkably in both treatment groups.